Free Will and Punishment: A Mechanistic View of Human Nature Reduces Retribution. (August 2014) - Shariff, Azim F.; Greene, Joshua D.; Karremans, Johan C.; Luguri, Jamie B.; Clark, Cory J.; Schooler, Jonathan W.; Baumeister, Roy F.; Vohs, Kathleen D.
If free-will beliefs support attributions of moral responsibility, then reducing these beliefs should make people less retributive in their attitudes about punishment. Four studies tested this prediction using both measured and manipulated free-will beliefs. Study 1 found that people with weaker free-will beliefs endorsed less retributive, but not consequentialist, attitudes regarding punishment of criminals. Subsequent studies showed that learning about the neural bases of human behavior, through either lab-based manipulations or attendance at an undergraduate neuroscience course, reduced people's support for retributive punishment (Studies 2–4). These results illustrate that exposure to debates about free will and to scientific research on the neural basis of behavior may have consequences for attributions of moral responsibility.